Humanistic nursing care management strategies: from formulation to implementation - Jing Lv; Yajie Su; Hongmei Tang; Xiaolin Jiang; Xiaojuan Chen (Frontiers in Public Health)
ObjectiveTo investigate the clinical implementation and effectiveness of the humanistic care nursing model, and to offer a reference for enhancing humanistic care practices in clinical settings.MethodsThree hundred and eighteen nurses and five hundred and two inpatients were selected as the control group and observation group before and after the implementation of humanistic care model in China from October to November 2023 and from May to June 2024. The differences of humanistic care ability, humanistic care behavior, medical narrative ability, nurses’ perception of the hospital’s attention to their caring ability, patients’ and nurses’ satisfaction, and patients’ evaluation of nurses’ caring behavior were compared between the two groups.ResultsAfter the implementation of the humanistic care model, the total score of nurses’ humanistic care ability, humanistic care behavior, medical narrative ability and scores of all dimensions were significantly increased, nurses’ perception of the hospital’s attention to their caring ability was significantly increased, patients’ evaluation of nurses’ caring behavior was improved, and both patients’ and nurses’ satisfaction were increased, with statistical significance (p < 0.05).ConclusionThe implementation of humanistic care nursing model can effectively improve managers’ care for nurses, further improve nurses’ humanistic care ability, humanistic care behavior and medical narrative ability, patients have a higher evaluation of nurses’ caring behavior, and nurses’ and patients’ satisfaction has been improved.Implications for nursing managementWe recommend that hospital administrators not only provide care for patients but also extend their support to nurses. It is essential to continuously optimize the “care chain” among nurse managers, nurses, and patients.